2016
DOI: 10.5194/acp-16-10621-2016
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of current and projected oil palm plantation expansion on air quality over Southeast Asia

Abstract: Abstract. Over recent decades oil palm plantations have rapidly expanded across Southeast Asia (SEA). According to the United Nations, oil palm production in SEA increased by a factor of 3 from 1995 to 2010. We investigate the impacts of current (2010) and near-term future (2020) projected oil palm expansion in SEA on surface-atmosphere exchange and the resulting air quality in the region. For this purpose, we use satellite data, high-resolution land maps, and the chemical transport model GEOS-Chem. Relative t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 52 publications
0
17
0
1
Order By: Relevance
“…Isoprene is believed to influence the atmospheric properties that control the condensation of water vapour, thus influencing cloud cover and rainfall (188). Isoprene contributes to a process that involves the generation of hydroxyl radicals which promotes smog and ozone in a polluted environment (190,191). Thus, we can predict that oil palm plantations will exacerbate air pollution in the vicinity of industrial centres with wider consequences for people and the environment.…”
Section: Volatile Organic Compounds From Oil Palmmentioning
confidence: 99%
“…Isoprene is believed to influence the atmospheric properties that control the condensation of water vapour, thus influencing cloud cover and rainfall (188). Isoprene contributes to a process that involves the generation of hydroxyl radicals which promotes smog and ozone in a polluted environment (190,191). Thus, we can predict that oil palm plantations will exacerbate air pollution in the vicinity of industrial centres with wider consequences for people and the environment.…”
Section: Volatile Organic Compounds From Oil Palmmentioning
confidence: 99%
“…Previous studies have shown that the sign and strength of the regional surface ozone response to increased isoprene strongly depend on availability of NO X (Ashworth et al, 2012;Silva et al, 2016;Warwick et al, 2013). When applying contemporary NO X emissions from published inventories, both Warwick et al (2013) applied future projections of oil palm expansion for biofuel production.…”
Section: Atmospheric Compositionmentioning
confidence: 99%
“…Both studies found that inflating the NO X emissions in the region of land conversion enhanced surface ozone concentrations (Ashworth et al, 2012;Warwick et al, 2013). In a study focused on estimating the air quality impacts associated with 2010 oil palm cover compared to a no-oil-palm 30 landscape, Silva et al (2016) simulated increased surface ozone concentrations over much of the region. They found that some low-NO X regions (e.g., parts of Borneo) exhibited surface ozone reductions in response to increased isoprene emissions (Silva et al, 2016).…”
Section: Atmospheric Compositionmentioning
confidence: 99%
See 2 more Smart Citations